COMPARATIVE ANALYSIS OF VOLATILITY OF CRYPTOCURRENCIES AND FIAT MONEY - G. O. Krylov (Финансы: теория и практика, 2018)
The article provides a comparative analysis of the volatility of the leading national fiat currencies and their transnational anonymous analogues, which received the slang name “cryptocurrency”.Volatility is the most important financial indicator in the management of financial flows, as a measure of the risk of using a financial instrument at a specified period of time. Cryptocurrency mining technology is available to the general public and has become an innovative phenomenon. The latest fi phenomena need to be investigated, so it is necessary to conduct a multilateral scientific analysis, identification and comparison of cryptocurrency with fi currency. The aim of this study is to obtain new estimates of cryptocurrency based on the use of tools such as GARCH-model, simple historical volatility (SHV) and developed by the author’s toolkit, which is based on the Chaikin method. The methodological basis of the research is logical, econometric, economic and statistical methods of analysis, technical and fundamental analysis, and method of scientific visualization. The calculated volatility estimates are based on the Central Bank’s data on currency rates and investigated using named three models. The article for the first time presents the results of comparison of volatility of the leading fiat currencies (uS dollar, euro, Chinese yuan and Japanese yen) and the most popular today so-called cryptocurrencies (bicoin, litecoin, ethereum, and monero). Estimation of volatility showed that the volatility of bitcoin is significantly higher than fiat money. In this regard, it is concluded that the recognition of cryptocurrency, in particular bitcoin, as a real money is premature, not only due to the lack of regulations of a certain cryptocurrency as a legal tender, but also on the grounds of violation of essential requirements for the properties of the currency, such as a low level of volatility.